Mitochondrial dysfunction RAD51, and Ku80 proteolysis promote apoptotic effects of Dinaciclib in Bcl‐xL silenced cells. Issue 4 (30th December 2017) - Premkumar, Daniel R.; Jane, Esther P.; Thambireddy, Swetha; Sutera, Philip A.; Cavaleri, Jonathon M.; Pollack, Ian F.
Abstract : In the present study, we investigated the effect of CDK inhibitors (ribociclib, palbociclib, seliciclib, AZD5438, and dinaciclib) on malignant human glioma cells for cell viability, apoptosis, oxidative stress, and mitochondrial function using various assays. None of the CDK inhibitors induced cell death at a clinically relevant concentration. However, low nanomolar concentrations of dinaciclib showed higher cytotoxic activity against Bcl‐xL silenced cells in a time‐ and concentration‐dependent manner. This effect was not seen with other CDK inhibitors. The apoptosis‐inducing capability of dinaciclib in Bcl‐xL silenced cells was evidenced by cell shrinkage, mitochondrial dysfunction, DNA damage, and increased phosphatidylserine externalization. Dinaciclib was found to disrupt mitochondrial membrane potential, resulting in the release of cytochrome c, AIF, and smac/DIABLO into the cytoplasm. This was accompanied by the downregulation of cyclin‐D1, D3, and total Rb. Dinaciclib caused cell cycle arrest in a time‐ and concentration‐dependent manner and with accumulation of cells in the sub‐G1 phase. Our results also revealed that dinaciclib, but not ribociclib or palbociclib or seliciclib or AZD5438 induced intrinsic apoptosis via upregulation of the levels of pro‐apoptotic proteins (Bax and Bak), resulting in the activation of caspases and cleavage of PARP. We also found an additional mechanism for the dinaciclib‐induced augmentation of apoptosis due to abrogation RAD51‐cyclin D1 interaction, specifically proteolysis of the DNA repair proteins RAD51 and Ku80. Our results suggest that successfully interfering with Bcl‐xL function may restore sensitivity to dinaciclib and could hold the promise for an effective combination therapeutic strategy.